A new approach for the comprehensive grading of petroleum reserves in China: Two natural gas examples. (1st January 2017) - Li, Wandi; Luo, Dongkun; Yuan, Jiehui
Abstract: For orderly and sustainable development, petroleum resources should be planned scientifically. Based on the discount cash flow (DCF) method, we propose a new approach for the comprehensive grading of petroleum reserves in China because existing reserve classification methods are unable to support the formulation of exploitation planning. This approach combines five factors: economic value, technological progress, subsidy policy, reserve scale and resource risk. Examples show that this approach can be used to grade natural gas resources rapidly and effectively, which is helpful for providing effective guidance for the scientific development of gas resources. Highlights: We investigated the existing representative reserve classification systems. Existing classifications are unable to support the formulation of exploitation. We established a new comprehensive approach for grading petroleum reserves. Two natural gas examples are used to demonstrate how to apply the proposed method. The approach is helpful for rapidly and effectively grading natural gas resources.